КУЛЬТУРА СКАСУВАННЯ: ЕТИЧНИЙ ТА ПОЛІТИЧНИЙ АСПЕКТИ (ДО ПОСТАНОВКИ ПРОБЛЕМИ У КОНТЕКСТІ РОСІЙСЬКО-УКРАЇНСЬКОЇ ВІЙНИ) - Korobko, Margaryta; Mishchenko, Anna (Ukrainian Cultural Studies, 2023)
Today Ukraine is struggling with the war on its own territory. Russian invasion has provoked many discussions in the cultural sphere. In the end of February 2022 Ukraine’s Minister of Culture and Information Policy Oleksandr Tkachenko called the world to impose cultural sanctions on the Russian Federation. It means to cancel Russian culture. Cancel culture refers to the popular practice of withdrawing support for (canceling) public figures and companies after they have done or said something considered objectionable or offensive. Cancel culture is generally discussed as being performed on social media in the form of group shaming. What ethical issues this phenomenon implicates? What does it mean for Ukraine? Cancel culture is a complicated phenomenon in the modern world. We can begin our analysis of the contemporary problem of the culture of cancellation in ethics and politics by analyzing the classic works of Hannah Arendt, Isaiah Berlin, and Michael Oakeshott. Oleksandr Klekovkin, a Ukrainian theater expert, actively promotes the idea of abolishing Russian culture in Ukraine. American lawyer Alan Dershowitz sees a negative aspect of the cancel culture phenomenon. So far, a clear understanding of this phenomenon has not been developed academically. The purpose of the article is an attempt to analyze the phenomenon of "cancellation culture" in ethical and political aspects, actualized in the conditions of the Russian-Ukrainian war in the context of the cancellation of Russian culture in Ukraine. If in a certain society, even under the conditions of a democratic political regime, the idea of at least a hypothetical possibility of solving all problems prevails, it will stop at nothing to achieve such an ideal state. This is the lesson we should have learned after two world wars. However, in practice, in many modern societies, there are again attempts to instill value monism, which manifests itself as "cancel culture". By legitimizing "cancel culture" as a modern trend, political systems significantly limit discursiveness and pluralism within society. After all, it becomes too uncomfortable to express an opinion that contradicts the generally accepted one. This threatens career, social status, and sometimes even safety.